2021
DOI: 10.15406/jabb.2021.08.00257
|View full text |Cite
|
Sign up to set email alerts
|

A review article on role of information and communication technology in agriculture and factors affecting its dissemination in Nepal

Abstract: The information and communication technology (ICT) is vital for the farming communities to intensify agricultural development in Nepal. This review presents the research in ICT highlighting the role of ICT in the agriculture sector and various factors affecting the dissemination process. About 60.4% of the total population is dependent on agriculture in Nepal. However, due to lack of awareness and higher cost of technology, the smallholder’s farmers are deprived of receiving the reliable and recent information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Information services could be effective by encouraging private sector to be involved in information dissemination using media, publications, extension materials, and training and visit programs. The finding is consistent to other studies (Bhusal et al, 2021).…”
Section: The Determinants Of Profit Efficiency In Vegetable Farmssupporting
confidence: 94%
“…Information services could be effective by encouraging private sector to be involved in information dissemination using media, publications, extension materials, and training and visit programs. The finding is consistent to other studies (Bhusal et al, 2021).…”
Section: The Determinants Of Profit Efficiency In Vegetable Farmssupporting
confidence: 94%
“…Therefore, Information has been said to be a resource that is key to growth and development which enhances sustainable development. Studies have shown that the commonly used ICT in the rural community includes Radio, mobile phone, and television (Javeed et al, 2020;Bhusal et al, 2021& Adeniyi, 2020. There is a geometric increase in the nation's teledensity which was 119% as of July 25, 2023, as affirmed by Adedapo (2023); this assertion stands to affirm the rapid growth of the mobile phone and other ICTs in the nooks and crannies of the country (Adeniyi & Yekinni, 2023) ICTs have been used for several interventions in developing nations with great benefits for its user, for instance, its utilization by rural dwellers of Bangladesh for Grameen Bank's village phone (VP) programme has boosted the income generation and social security of poor women (Meyenn & Lawson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Umukoro et al, (2021), the perception of the use of ICTs is the bedrock for its usefulness in society, especially among the genders of rural communities with diverse cultural diversity. The factors that could propel the right perception of ICTs utilization include the constraints to use, the benefits of use, the purpose of use, and the prevailing culture guiding gender and generation behaviours (International Telecommunication Union (ITU), 2020; Bhusal et al, 2021). The purpose for which rural dwellers deploy ICTs for include access to market information, and financial services, reducing rural-urban migration, and promoting gender equality (Javeed et al, 2020& Ramana, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that the use of ICTs by farmers was effective and was influenced by socio-economic and institutional factors. Bhusal et al, (2021) conducted a study on the role of ICT in agriculture sector in Nepal and revealed t hat farmers have low access to reliable and updated agricultural information sources. Chowhan & Ghosh (2020) conducted a study on the role of ICT in agriculture and its future scope in Bangladesh and found that farmers and extension staff have limited access, level of knowledge and capacity to use ICTs.…”
Section: Introductionmentioning
confidence: 99%